Eksplorasi efek etanol terhadap survival dan status imunitas Drosophila melanogaster - Rosa, Reski Amalia; Latada, Nadila Pratiwi; Asbah, Asbah; Mu'arif, Ahmad; Yulianty, Risfah; Nainu, Firzan (Pengurus Pusat Ikatan Apoteker Indonesia, 2021)
: High doses of ethanol in the body can elicit damage to organs including the brain, liver and kidneys. In addition, ethanol can trigger the formation of reactive oxygen species (ROS), where excess levels of ROS in the body can promote cell death through the apoptotic pathway. Apoptotic cells that are not phagocytosed will undergo necrosis. In the process of necrosis, cells release DAMPs, endogenous pro-inflammatory molecules and induce the core immune system in Drosophila that are homologues to humans, namely Toll, IMD (Immune Deficiency), and JAK-STAT (Janus Tyrosine Kinase-Signal Transducer and Activator of Transcription). The aim of this research is to investigate how ethanol exposure influences gene expression in the Toll, Imd, and JAK-STAT pathways. The results showed that ethanol could affect the survival rate of male and female Drosophila melanogaster w1118. Exposure to ethanol at high concentrations (85%) caused a decrease in the expression of Drs, but not the expression of the Dpt. In addition, TotA expression, but not Upd3, was amplified significantly as the ethanol concentration increased. In conclusion, Drosophila experienced a decrease in the survival rate due to ethanol exposure which might be related to the stress response and the immune system which is mediated by certain pathways.